Capri. - Bibliographisches Institut (Hildburghausen) (Hildburghausen : Bibliographisches Institut Hildburghausen, 1800)
Prikaz grebena u moru.
Dolje sredina ispod prikaza: CAPRI // Bibliograph. Institut in Hildburghausen.
Izvornik digitaliziran
Keywords: Nadorezi